PENERAPAN HUKUM PIDANA TERHADAP TINDAK PIDANA MAKAR OLEH ORGANISASI PAPUA MERDEKA (OPM) DI KABUPATEN JAYAWIJAYA (StudiPutusanNomor 38/Pid.B/2011/PN.Wmn) - Lani Sujiagnes Panjaitan; Alvi Syahrin; Marlina Marlina; Jelly Leviza (Universitas Sumatera Utara, 2016)
ABSTRACT A mutiny criminal act is related to a state security. A munity threats legal interest and the safety of Unitary State of the Republic if Indonesia as stipulated in Chapter I book II of Penal Code which consist of three form, namely the mutiny which attacks the legal interests for the safety of Head of State or his/her Vice (Article 104 Penal Code), the unity of State regions (Article 106 Penal code), and the enforcement of State Government (Article 107 Penal Code. The formulations of problem in the research are whether the act done by the Liberating Papua Organization (LPO) is classified as mutiny, how the legal responsibilities towards the mutiny criminal act done by the LPO in the District Of Jayawijaya are, how the implementation of penal code on the mutiny criminal act done by the LPO in District of Jayawijaya based on the verdict No.38/Pid.B/2011/PN.Wmn is. The research result showed the act done by the LPO was a mutiny stipulated in the article 106 Penal code an hasfullfilled the elements whose goal was to conquer the region of state fully or partly under the foreign government with the intetion to separate some parts of the state region. The existence of conscious cooperation. Consequently, all defendants subjected tho the same crimes. Implementation of penal code towards the mutiny criminal act done the LPO in the verdict No.38/Pid.B/2011.PN.Wmn that the judge has implemented the Article 106 Penal Code Jo Article 55 clause (1) in the 1st , namely by sentencing 8 years in prison to every member of LPO. Keywords : mutiny criminal, Liberating Papua Organization